High-Frequency Distortion-Product Otoacoustic Emission Repeatability in a Patient Population. Issue 1 (January 2018) - Dreisbach, Laura; Zettner, Erika; Chang Liu, Margaret; Meuel Fernhoff, Caitlin; MacPhee, Imola; Boothroyd, Arthur
Abstract : Objectives: Distortion-product otoacoustic emissions (DPOAEs) are repeatable over time at lower frequencies (⩽8 kHz) and higher frequencies (>8 kHz) in healthy, normal-hearing subjects. The purpose of this study was to examine the repeatability of DPOAEs measured with high-frequency (HF) stimuli in a patient population. It was hypothesized that HF DPOAEs would be repeatable over four trials. Design: DPOAEs were measured in 40 cystic fibrosis (CF) patients (17 females and 23 males) with measurable behavioral thresholds and present DPOAEs for at least 2 of the high frequencies tested (8 to 16 kHz). A depth-compensated simulator sound pressure level (SPL) method of calibration was utilized. Each patient attended four trials, in which a complete set of data were collected. At each trial, three different DPOAE paradigms were completed. First, a discrete frequency sweep was measured between 8 and 16 kHz with a ratio ( f 2 / f 1 ) of 1.2 and levels of 65/50 dB SPL for L 1 / L 2 . Next, ratio and level sweeps were obtained at the two highest frequencies with a present DPOAE determined from the discrete frequency sweep, and the results were used to calculate DPOAE group delay and DPOAE detection thresholds, respectively. Ratio sweeps were collected with f 2 / f 1 varied from 1.1 to 1.3 and stimulus levels of 60/45 dB SPL ( L 1 / L 2 ). Level sweeps were collected with an f 2 / f 1 of 1.22 and L 2 = 50 and L 1 varied between 20 and 70 dB SPL. Differences and correlations between trials, SE of the measurement, and confidence intervals were calculated, as well as a repeated-measures analysis of variance. Results: DPOAE response and behavioral threshold variability in CF patients were not significantly different across four trials. It can be expected in 95% of CF patients that differences between trials of DPOAE levels, group delay, and detection thresholds and behavioral thresholds are less than 6.26 dB, 0.87 msec, 9.34 dB, and 9.60 dB, respectively. Conclusions: HF DPOAEs were repeatable across four test trials for all three paradigms measured in a group of CF patients. These results are encouraging for the measurement of HF DPOAEs to be monitored in those exposed to ototoxic agents.